Efektivitas Sistem Pembelajaran Jarak Jauh dalam Meningkatkan Literasi Teknologi Pendidikan Islam di Daerah Rural (Studi di Sarolangun) - Damanik, Jainab Rayanti; Jamrizal, Jamrizal; Yunus, Abdullah (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The rapid advancement of digital technology, accelerated by the COVID-19 pandemic, has significantly transformed educational systems worldwide, including Islamic education in rural areas. However, implementing distance learning (DL) in these settings presents unique challenges due to limited infrastructure, low digital literacy, and socioeconomic disparities. This study aims to evaluate the effectiveness of distance learning in enhancing technological literacy within Islamic education in rural Sarolangun, Indonesia. A qualitative approach was employed through a systematic literature review, focusing on scholarly works related to distance education, digital literacy, and Islamic pedagogy in rural contexts. Data were gathered from academic databases using keywords such as "distance learning," "digital literacy," "Islamic education," and "rural area." The findings reveal that while digital platforms can effectively support cognitive learning, they often fall short in addressing affective and psychomotor domains crucial to Islamic education. The study also highlights the importance of integrating Islamic values into digital pedagogy to maintain spiritual authenticity. The research suggests that blended learning models combining online and face-to-face approaches offer a more adaptable solution for rural Islamic schools. Nevertheless, ongoing challenges such as technological inequity, insufficient teacher training, and cultural resistance to change must be addressed. These insights provide a foundation for designing contextually relevant and value-based distance education strategies that align with the needs and realities of rural Muslim communities.